Evaluation of the Architectural Features and Physical Environment in Early Childhood Education Framework - Shirin Izadpanah; Poupak Parvaresh; Yaren Şekerci (Civil Engineering Journal, 2021)
Many initial childhood settings worldwide have started to create an environment and educational system that would increase the children’s environmental awareness and the ways to minimize it. A newly built ecological kindergarten in Antalya, Turkey, has adopted an educational system in which children are getting involved with nature in most of their daily routines. This study intended to learn if the physical environment of the declared setting responds to the early childhood environmental education work frame. Accordingly, the study has adopted “Guidelines for Excellence, Early Childhood Environmental Education Programs’’ as the primary resource for an evaluation checklist. Data collection is conducted via an in-depth site analysis, as well as the questionnaire survey of teachers and parents regarding their perception of the kindergarten’s physical environment. The results showed that the physical environment of the kindergarten does not meet the requirements of the early education environmental framework. This study underlines the importance of profound research studies that analyze the architectural features of an early environmental education setting and the ways improving its physical attributes may promote the children environmental education. Doi: 10.28991/cej-2021-03091657 Full Text: PDF